Crime Related Use of Benzodiazepine in District Peshawar (Medical Forum Monthly, 2024)
Background: The number of reported crime in which the victims were first rendered unconscious; lacking awareness of his or her surrounding and later the planned crime ensued. Blood and urine samples were collected and tested for sedative hypnotics at the toxicology lab. The specimens, all of them were tested positive for benzodiazepine.Study Design: Cross Sectional study.Place and Duration of Study: This study was conducted at Toxicology Laboratory, Department of Forensic Medicine and Toxicology, Khyber Medical College, Peshawar from 01.01.2010 to 31.12.2010.Materials and Methods: The study was conducted on 77 samples of urine and blood obtained from the victims who were brought over by police to the tertiary care hospitals in district Peshawar.Results: The procedure to find out the exact subtype was with the help of High Performance Liquid Chromatography (HPLC) in the Toxicology laboratory. The chemical analysis revealed that all the samples obtained from the victims carried Clonazepam a subtype of Benzodiazepine.Conclusion: Easy availability of benzodiazepine and other narcotic analgesics across the country renders these technically dangerous medicines into the hands of criminals resulting in heinous and monstrous consequences.